KESENJANGAN GENDER DALAM PEMENUHAN HAK ASASI MANUSIA DI INDONESIA: FAKTOR PENYEBAB DAN SOLUSI - Sultona, Saihoh (Legal Studies Journal, 2025)
The gender gap in access to and fulfillment of human rights (HAM) in Indonesia is a significant issue that continues to grow and hinders women's full participation in society. Even though Indonesia has a constitution that guarantees gender equality, patriarchal social and cultural norms still limit women's freedom and opportunities in various sectors, including education, economics, politics and legal protection. Discrimination which takes the form of wage inequality, gender-based violence, and limited access to education and health prevents women from achieving independence and prosperity. Therefore, it is important to implement legal reforms, improve gender equality education, and create more inclusive policies. This research aims to identify forms of gender inequality and the factors that cause them, through literature reviews and normative legal research techniques. The results of this research show that cultural, economic, educational, legal and political factors play a major role in exacerbating gender inequality in Indonesia, and an integrated solution is needed to overcome this problem.